The time paradox of emergency medicine: Another inverted U curve - Fatovich, Daniel (Wiley-Blackwell Publishing Asia, 2017)
© 2017 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine Time is integral to emergency medicine, but the importance of time is over-rated. Media promotes a focus on time over suffering. Terms such as the ‘golden hour’ and ‘time is muscle’ are embedded into our language, but is language that corrupts thought. Time-based metrics for ED quality measures focus on speed over accuracy, reflecting another inverted U curve in our system of care. We often fail to understand the importance of heterogeneity, and the heterogeneity of treatment effect, for example, sicker patients are more likely to benefit from the intervention, whereas less sick patients do not benefit but are more likely to be harmed. This highlights the importance of nuanced judgements. We need to get into the Goldilocks zone of the ‘just right’ balance between speed and accuracy. This essay challenges us to focus more on the suffering human subject, rather than on time-based metrics that reflect our hope bias.